Prevalence and hematological characteristics of bacterial vaginosis in postmenopausal women - Purnamasari, Yenti; Hamid, Firdaus; Saimin, Juminten; Bukhari, Agussalim (Journal of Associated Medical Sciences, 2025)
Background: Bacterial vaginosis (BV) is a common vaginal dysbiosis associated with systemic inflammatory responses. However, its hematological impact in postmenopausal women remains unclear. This study investigates hematological parameters in postmenopausal women with BV to assess potential systemic inflammatory alterations. Objectives: This study aimed to investigate various hematological parameters across different BV conditions to better understand their potential role in BV diagnosis and pathophysiology. Materials and methods: A total of twenty-five postmenopausal women were recruited and categorized into three groups: bacterial vaginosis (BV), intermediate vaginal microbiota, and healthy vaginal microbiota based on Nugent scoring. Vaginal samples were collected aseptically with the participants in the lithotomy position by swabbing the vaginal walls circumferentially near the cervical fornix. Nugent scoring was performed on Gram-stained smears to classify the subjects. Subsequently, Verify® urinalysis reagent strips were directly applied to the vaginal wall to measure pH, protein, and glucose levels. Additionally, hematological parameters including leukocyte count, lymphocyte, eosinophil, neutrophil, monocyte, basophil, platelet counts, and platelet-to-lymphocyte ratio (PLR) were assessed from peripheral blood samples. All data were statistically analysed and compared among the three groups using ANOVA and Kruskal–Wallis tests, with a significance level set at p<0.05. Results: The prevalence of BV in postmenopausal women was 72%. Hematology parameters did not show significant differences across BV, intermediate, and healthy groups (p>0.05). Leukocyte, neutrophil, and PLR values were slightly higher in BV cases, but not to a statistically significant degree. These findings suggest that BV in postmenopausal women may not elicit strong systemic inflammatory responses compared to premenopausal populations. Additionally, pH, glucose, and protein levels did not differ significantly among the groups, highlighting the need to reconsider standard vaginal health biomarkers in postmenopausal women due to physiological changes induced by menopause. Conclusion: The prevalence of bacterial vaginosis (BV) in this study was higher than that reported in previous studies; however, it was not associated with significant hematological alterations. Further research is needed to identify reliable systemic and vaginal biomarkers for BV diagnosis in this population, considering the potential influence of hormonal and immunological factors.